Review: - Determination of vitamin E concentration in different samples - Mezaal, Elham N.; Mohammed, Maha A.; Sadiq, Kawther Ahmed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Vitamins are a type of essential and important nutrient in the human body. It also plays an essential role in the health and protection of the human body. They share physiological functions with many chemicals, and their deficiency or increase endangers human health. Therefore, it is required to evolve and use modern methods to estimate the concentration of vitamins, even if their concentration is very low, and these include the vitamin E group tocopherols, tocotrienols, isomers, esters, and derivatives. They disagree not in their ability as anti-cancer agents but rather in their physiological as well as chemical relations, unlike vitamin A and vitamin D. The richest source of vitamin E is vegetable oil. Vitamin E, classified as a vitamin, dissolves in fat. It is pointed out in different types of foods involving vegetable oils, meat, eggs, cereals, and poultry, in addition to fruits. Some of the vital signs and symptoms of a vitamin E deficiency include neurological defects such as dysfunction of the brain, nerves, spinal cord, and muscles; muscle pain and weakness; muscle deterioration, including cardiomyopathy or weak heart muscle; low birth weight; difficulty moving the eyes up and down; poor vision at night; loss or lack of sense of vibration; and a feeling of numbness or tingling.